1975
DOI: 10.1213/00000539-197509000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of Lorazepam Delirium by Physostigmine

Abstract: Two adult patients suffered postoperative delirium following administration of lorazepam, a new benzodiazepine sedative. Physostigmine was found effective in reversing all untoward central nervous system effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

1982
1982
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 0 publications
0
7
0
1
Order By: Relevance
“…Anticholinergic drugs can induce delirium and often contribute substantially to the delirium seen in hospitalized patients 16. Increasing acetylcholine levels by use of cholinesterase inhibitors such as physostigmine has been shown to reverse delirium associated with anticholinergic drugs 1719. Serum anticholinergic activity, which reflects anticholinergic influences of both endogenous and exogenous drugs and their metabolites, has been shown in some studies to be increased in patients with delirium and to decline with the resolution of delirium 2022.…”
Section: Pathophysiologymentioning
confidence: 99%
“…Anticholinergic drugs can induce delirium and often contribute substantially to the delirium seen in hospitalized patients 16. Increasing acetylcholine levels by use of cholinesterase inhibitors such as physostigmine has been shown to reverse delirium associated with anticholinergic drugs 1719. Serum anticholinergic activity, which reflects anticholinergic influences of both endogenous and exogenous drugs and their metabolites, has been shown in some studies to be increased in patients with delirium and to decline with the resolution of delirium 2022.…”
Section: Pathophysiologymentioning
confidence: 99%
“…During the first 23 h postsurgical he used a total of 1110 mg were not warranted. Although (9,22). Throughout this period the nursing observations indicated that the patient two days later.…”
Section: Introductionmentioning
confidence: 84%
“…(1). Although (9,22). Hepatic N-demethylation enzyme-inducing the blood concentrations of both norpethidine and agents such as loperamide (a piperidine derivative pethidine contribute to the variation in the intensity and congener of pethidine) and carbamazepine may of CNS excitation, the norpethidine concentration increase the formation of norpethidine (2,10,23).…”
Section: Case Reportmentioning
confidence: 99%
“…Наиболее часто причиной делирия считают наруше-ние функционирования холинергической системы [29], и это обосновывается целым рядом факторов [35][36][37][38][39][40][41]. Есть также упоминание [42] о нарушении функционирования дофаминергической системы, а также о дисбалансе дофаминовой и холинергиче-ской систем.…”
Section: этиология и патогенезunclassified